Serum concentrations of leptin and adiponectin in dogs with chronic kidney disease. (27th May 2022) - Choi, Dongjoon; Yun, Taesik; Lee, Dohee; Koo, Yoonhoi; Chae, Yeon; Yang, Mhan‐Pyo; Kang, Byeong‐Teck; Kim, Hakhyun
Abstract: Background: An imbalance in adipokines is associated with the progression of chronic kidney disease (CKD) in humans. However, alterations in adipokines in dogs with CKD remain unclear. Objectives: To examine whether adipokine concentrations in serum differ between healthy dogs and dogs with CKD and to determine the correlation between serum adipokine concentrations and CKD severity in dogs. Animals: Twenty dogs with CKD and 10 healthy dogs. Methods: In this cross‐sectional study, serum concentrations of leptin, adiponectin, interleukin (IL)‐6, IL‐10, IL‐18, and tumor necrosis factor (TNF)‐α were measured in healthy dogs and dogs with CKD, which were classified according to the International Renal Interest Society guidelines. Results: Serum leptin concentrations were positively correlated with systolic arterial blood pressure ( r = .41), creatinine concentrations ( r = .39), and symmetric dimethylarginine concentrations ( r = .73). Serum adiponectin concentrations (median [range]) in CKD dogs with borderline or non‐proteinuric (20.25 [14.9‐45.8] ng/mL) were significantly higher than those in proteinuric CKD dogs (13.95 [6.4‐22.1] ng/mL; P = .01). Serum IL‐6 (median [range]; 43.27 [24.30‐537.30] vs 25.63 [6.83‐61.03] pg/mL; P = .02), IL‐18 (median [range]; 25.98 [11.52‐280.55] vs 10.77 [3.53‐38.45] pg/mL; P = .01), and TNF‐α (median [range]) concentrations (11.44 [8.54‐38.45] vs 6.105 [3.97‐30.68] pg/mL; P = .02) were significantly different between proteinuric and borderline or non‐proteinuric CKD dogs. Conclusions and Clinical Importance: leptin and adiponectin concentrations in serum might be associated with severity of CKD and proteinuria in dogs with CKD, respectively.